A válaszálcázás kiküszöbölése: (Hibával mért diszkrét adatok statisztikai elemzése a társadalomtudományokban) - Bornemisza, Eszter; Csepeli, György (Szociológiai Szemle, 2024)
This article has attempted to validate randomized response models. W arner has developed a method for investigation of „sensitive” issues. This method was applied on a sample of individuals where we have already known the distribution of responses in relation to a given sensitive issue. Results of validation have demonstrated efficiency: observed distribution fitted to real distribution.